Desvinculado y Desigual: Is Segregation Harmful to Latinos?. Issue 1 (July 2015) - Steil, Justin; De la Roca, Jorge; Ellen, Ingrid Gould
Despite the high levels of metropolitan-area segregation that Latinos experience, there is a lack of research examining the effects of segregation on Latino socioeconomic outcomes and whether those effects differ from the negative effects documented for African Americans. We find that segregation is consistently associated with lower levels of educational attainment and labor market success for both African American and Latino young adults compared with whites, with associations of similar magnitudes for both groups. One mechanism through which segregation may influence outcomes is the difference in the levels of neighborhood human capital to which whites, Latinos, and African Americans are exposed. We find that higher levels of segregation are associated with lower black and Latino neighborhood exposure to residents with college degrees, relative to whites. We also find support for other commonly discussed mechanisms, such as exposure to neighborhood violent crime and the relative proficiency of the closest public school.